beheadings, causes, factors, pun Pembegalan yang makin merajalela di indonesia - Rahmawati, Elif Thoyyibah (Maliki Interdisciplinary Journal, 2025)
This research aims to find out cases that are not in accordance with the precepts of Pancasila which is the basis of our beloved country. It was found that the case of beheading offended the precepts of Pancasila, and this beheading was very many types as well as the causative factors. However, the punishment that will be imposed on the perpetrators is not inversely proportional to human rights. The essence of the cause of this beheading is the lack of devotion to God Almighty, because everything we do comes from our hearts. That is the proof of his pentine for us to understand and practice all the knowledge we get in terms of goodness.